Assessment of genotypic diversity among Fusarium culmorum populations on wheat in Iran - POUZESHIMIAB, Behnam; RAZAVI, Mohammad; ZAMANIZADEH, Hamid Reza; ZARE, Rasoul; REZAEE, Saeed (Phytopathologia Mediterranea, 2014)
Fusarium culmorum is one of the most important causal agents of crown rot of wheat in the north and northwest of Iran. Eight pairs of single-locus microsatellite primers were used to analyze genomic DNA of 88 isolates of F. culmorum collected from wheat fields in five provinces of Iran. Thirty-three alleles were detected among eight simple sequence repeat (SSR) loci, ranging from 2–6 alleles (with an average of 4.125 alleles/locus). Eighty-four multilocus genotypes were detected among 88 isolates of F. culmorum, indicating a high level of genetic diversity among isolates. Nei’s gene diversity of populations ranged from 0.355 to 0.561 with an average of 0.47. The greatest genetic similarity (0.8409) was detected between the Qazvin-East Azarbaijan and Golestan populations, the greatest genetic distance was between the Tehran and Golestan populations. These results show that SSR is a convenient and rapid technique for the analysis of genetic diversity and strain differentiation of F. culmorum.